Siderophore production by Staphylococcus aureus and identification of iron-regulated proteins. - Courcol, R J (1997)
Siderophore activity of Staphylococcus aureus was detected in an iron-restricted chemically defined medium. The molecular mass of this siderophore, called aureochelin, was 577 Da. Surface-associated proteins of 120, 88, 57, 35, and 33 kDa were mainly expressed under iron restriction conditions. Results showed a relationship between siderophore production and the existence of the 120- and 88-kDa proteins. Western blotting of surface-associated proteins revealed that these proteins were recognized both by patients sera and polyclonal rabbit serum.